2023
DOI: 10.1021/acs.inorgchem.3c00279
|View full text |Cite
|
Sign up to set email alerts
|

From Laves Phases to Quasicrystal Approximants in the Na–Au–Cd System

Abstract: The exploratory synthesis of gold-based polar intermetallic phases has revealed many new compounds with unprecedented crystal structures, unique bonding arrangements, and interesting electronic features. Here, we further understand the complexity of gold’s crystal chemistry by studying the Na–Au–Cd ternary composition space. A nearly continuous structure transformation is observed between the seemingly simple binary NaAu2–NaCd2 phases, yielding three new intermetallic compounds with the compositions Na­(Au0.89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…These foundational structure types serve as a framework for analyzing Sc­(Os 2– x Si x ) and ScOs 2 Si 2 , thereby enhancing our understanding of their structural characteristics. The MgZn 2 -type structure is a classic representation of the C14 Laves phase (Figure a) with two distinct structural units: trigonal-bipyramidal Zn units that share vertices extending into the c -axis, and Mg centering a face-sharing Friauf truncated tetrahedron. , The literature indicates that Sc can occupy the Mg site and Os can occupy the Zn sites forming ScOs 2 . Prior research has also demonstrated that the Zn sites can accommodate mixed occupancy of transition metal atoms and silicon atoms, resulting in the ordered variant Mg 2 Cu 3 Si-type structure. , During the synthesis here, two compounds, ScOs 1.62 Si 0.38 and ScOs 1.39 Si 0.61 were found to crystallize in the Mg 2 Cu 3 Si-type structure (space group P 6 3 / mmc ), as illustrated in Figure b,c.…”
Section: Resultsmentioning
confidence: 99%
“…These foundational structure types serve as a framework for analyzing Sc­(Os 2– x Si x ) and ScOs 2 Si 2 , thereby enhancing our understanding of their structural characteristics. The MgZn 2 -type structure is a classic representation of the C14 Laves phase (Figure a) with two distinct structural units: trigonal-bipyramidal Zn units that share vertices extending into the c -axis, and Mg centering a face-sharing Friauf truncated tetrahedron. , The literature indicates that Sc can occupy the Mg site and Os can occupy the Zn sites forming ScOs 2 . Prior research has also demonstrated that the Zn sites can accommodate mixed occupancy of transition metal atoms and silicon atoms, resulting in the ordered variant Mg 2 Cu 3 Si-type structure. , During the synthesis here, two compounds, ScOs 1.62 Si 0.38 and ScOs 1.39 Si 0.61 were found to crystallize in the Mg 2 Cu 3 Si-type structure (space group P 6 3 / mmc ), as illustrated in Figure b,c.…”
Section: Resultsmentioning
confidence: 99%